PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MODEL PEMBELAJARAN DISKURSUS MULTI REPRESENTASI MATERI SISTEM REPRODUKSI MANUSIA - Dinar, Sri Putri; Mustami, Muhammad Khalifah; Hamansah, Hamansah (Jurnal Biotek, 2021)
This research and development (R & D) aimed 1) to find out how to develop LKPD based on the Diskursus Multi Representasi (DMR) learning model on the human reproductive system material, and 2) to determine the validity level of LKPD based on the Diskurus Multi Representasi (DMR) learning model on the material of the human reproductive system. This research produced a student worksheet (LKPD) based on the Diskursus Multi Representasi learning model (DMR). The research model referred to the 4-D Thiagarajan development model. The model consists of four stages, namely: define, design, develop, and disseminate. The research instrument used was a validation sheet to obtain product validity data. Based on the results of the validator's assessment, the validity level of LKPD based on the Diskurus Multi Representasi (DMR) learning model on the human reproductive system is in the very valid category with an average value of 3.93 (3,5 ≤ V≤ 4). This indicates that LKPD based on the learning model is feasible to use.